STATUS OF AGRICULTURE, FORESTRY, FISHERIES AND NATURAL RESOURCES HUMAN RESOURCE IN CEBU AND BOHOL, CENTRAL PHILIPPINES - Rica, Rachel Luz V.; Delan, Gloria G.; Monte, Irene A.; Tan, Ester V. (Journal of Agriculture and Technology Management, 2018)
This  paper  aimed  to  present  the  current  status  of  agriculture,  forestry,  fisheries  and natural resources (AFNR) human resource in the two provinces of Cebu and Bohol, Central Philippines in order to understand the reasons in the persistent downtrend of enrolment and graduation in these sectors. Cross-sectoral investigation of the three groups of respondents was conducted to in-school students, graduates and employers of AFNR. Primary and secondary data were   gathered   and   analyzed   descriptively.   Findings   revealed   a   persistent   downtrend   in enrollment and graduation trends for the past ten years. Intervening economic, socio cultural, issues and policies impacted negatively the enrollment in AFNR. Fisheries registered the highest rate of decline in terms of enrollment and graduates. Currently enrolled students indicate that number one reason in choosing a degree in AFNR is the provision of scholarship, while graduates indicated that they took up the course because of its popularity in their community. Future pl ans of respondents contradict since majority of in-school students plan to apply for job overseas, while the graduates are not currently applying for a job overseas. Majority of the employed graduates landed in local-private companies with temporary or contractual status.  Employers of these graduates are distributed in the urban areas within the region.